2000
DOI: 10.1007/s004210050035
|View full text |Cite
|
Sign up to set email alerts
|

In vivo 4-androstene-3,17-dione and 4-androstene-3β,17β-diol supplementation in young men

Abstract: To determine if known androgenic hormone precursors for testosterone in the androgen pathway would be readily transformed to testosterone, eight male subjects [mean age 23.8 (SEM 3) years, bodymass 83.1 (SEM 8.7) kg, height 175.6 (SEM 8.5) cm] underwent a randomized, double-blind, cross-over, placebo-controlled oral treatment with 200 mg of 4-androstene-3,17-dione (delta 4), 4-androstene-3 beta,17 beta-diol (delta 4 Diol), and placebo (PL). The periods of study were separated by 7 days of washout. Blood was dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 7 publications
5
22
0
Order By: Relevance
“…Related studies examined the acute effect of orally administered testosterone prohormones such as androstenedione and androstenediol, which did not result in uniform findings concerning the elevation of plasma testosterone concentrations of young healthy men (King et al, 1999;Brown et al, 2000;Earnest et al, 2000. In accordance to our results, an increase of plasma testosterone concentrations after sublingual androstenediol intake was reported (Brown et al, 2002), demonstrating the effectiveness of this route of drug administration.…”
Section: Discussionsupporting
confidence: 80%
“…Related studies examined the acute effect of orally administered testosterone prohormones such as androstenedione and androstenediol, which did not result in uniform findings concerning the elevation of plasma testosterone concentrations of young healthy men (King et al, 1999;Brown et al, 2000;Earnest et al, 2000. In accordance to our results, an increase of plasma testosterone concentrations after sublingual androstenediol intake was reported (Brown et al, 2002), demonstrating the effectiveness of this route of drug administration.…”
Section: Discussionsupporting
confidence: 80%
“…Work by Earnest et al (2000) has demonstrated that oral administration of A-dione and A-diol can signi®cantly increase plasma total and free T. However, chronic administration of 300 mg/day of androstenedione for 8 weeks has also been shown to elevate serum estradiol and estrone in men, as is already known to occur in women (Gompel et al 1986;King et al 1999). Thus, one might also speculate that any anabolic eect of A-dione may be oset by the rise in plasma estrogens.…”
Section: Edione (A-dione) and Androstenediol (A-diol) T And 19-mentioning
confidence: 91%
“…Athletes ingest these particular supplements in the belief that their conversion into T will increase anabolic processes and help build up skeletal muscle mass. A study by Earnest et al (2000) examined the acute eects of oral treatment with 200 mg of 4-androstene-3,17-dione, 4-androstene-3 beta,17 beta-diol, and placebo (PL) on peripheral plasma T concentration. They found that both androstenedione and androstenediol signi®cantly increased the T concentration when compared to a placebo.…”
Section: Introductionmentioning
confidence: 99%
“…Ingesting 100 or 200 mg doses of androstenedione Ballantyne et al 2000;Brown et al 2000b;Leder et al 2000;Rasmussen et al 2000) or androstenediol (Earnest et al 2000) does not acutely alter serum testosterone concentrations in eugonadol men. However, Leder et al (2000) observed that in 2 out of 14 healthy men who consumed a single dose of 300 mg androstenedione, serum testosterone concentrations were acutely elevated by as much as fourfold.…”
Section: Introductionmentioning
confidence: 96%